2018
DOI: 10.1530/erc-17-0182
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib sensitizes thyroid cancer to BRAF inhibitor in vitro and in vivo

Abstract: Although overall survival rate for patients with thyroid cancer (TC) is high, there is an alarming 10-year recurrence rate of up to 30% conferring a ~50% survival among these high-risk patients. The BRAF mutation is estimated to be present in over 50% of papillary thyroid cancer (PTC) cases besides being associated with carcinogenesis and poor prognosis. We assessed the status of NF-κB, Ki-67, cyclin D1 and BRAF in TC tissues and TC cell lines using immunohistochemistry and Western blot analysis. Concurrently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…A novel preclinical study of mebendazolen demonstrated that it had promising therapeutic implications for patients with treatment refractory papillary thyroid cancer [12]. Treatment with the combination of the BRAF inhibitor Vemurafenib and Bortezomib accelerate mitochondrial dysregulation and apoptosis of TC cells Endocrine Journal Advance Publication [13]. But these drugs are not widely applied to in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A novel preclinical study of mebendazolen demonstrated that it had promising therapeutic implications for patients with treatment refractory papillary thyroid cancer [12]. Treatment with the combination of the BRAF inhibitor Vemurafenib and Bortezomib accelerate mitochondrial dysregulation and apoptosis of TC cells Endocrine Journal Advance Publication [13]. But these drugs are not widely applied to in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zecchin and colleagues clearly demonstrated that proteasome inhibitors possess a significant selectivity toward BRAF V600E -mutant colorectal cancer cells as a consequence of persistent BRAF signaling and a nononcogenic addiction to the proteasome function in those cells [57]. Furthermore, the combination of bortezomib and vemurafenib was shown to produce synergistic antitumor effects in thyroid cancer, both in vitro and in a xenograft model [58]. In the present study, we show that our vemurafenib-resistant cells were more sensitive to bortezomib than parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the doses of the two drugs were reduced in the animal model, while the synergistic antitumour effects were preserved. In vitro assays studying the invasion suggested that the treatment could also play a role in the metastatic process [57]. The redifferentiation of cells harboring the BRAF V600E mutation was reported to be associated with an increase of radioiodine uptake and was evaluated with the combination of BRAF/MEK inhibitors (dabrafenib/selumetinib) and HER1/2 inhibitor (lapatinib).…”
Section: Combination To Mapk/mek Inhibitorsmentioning
confidence: 99%